El libro de texto como ejercicio decolonial para la enseñanza de las ciencias naturales: Un análisis intercultural (Memorias Sifored - Encuentros Educación UAN, 2021)
The following investigation for doing an analysis of intercultural school text of a production of authorship of the Nasa community. The text includes scientific knowledge or universal knowledge as the text calls it, recognizing the importance of dialogue, a questioning is made about the relationship between the production of the text El Manto de Mama Kiwe and the educational community, based on an interpretive methodology organized in two large categories, intertextual and extratextual, the first one allowed the review of the book in terms of the sources of knowledge, the intention of the book, the illustrations, etc. and the extratextual one, which involves the thought and form of construction of the text by teachers . Finally, it is found that the school text that is reviewed is an effort to claim the community's own knowledge, to maintain a fight against homogenization and political imposition, in turn, the need to recognize the context as a fundamental axis for the construction of school supplies such as textbooks.
Keywords: Textbooks; science teaching; interculturality